A Long Time Ago in a Library Far, Far Away ... The Adventures of the Gladiatoria Manuscript from New Haven - Dierk Hagedorn (Bern Open Publishing, 2015)
In this paper I will describe the adventurous history of an important late medieval German fechtbuch-a fighting manual-that belongs to a number of manuscripts known as the Gladiatoria group. In the beginning, the extent and the characteristics of this group of codices are explained; later on I will deal with one specific specimen that formerly belonged to a library in Germany-the Herzogliche Bibliothek in Gotha-from where it vanished during or after World War II. Until quite recently this manuscript was believed to be lost. I was able to identify a Gladiatoria manuscript from the Yale Center for British Art in New Haven, Connecticut, as that missing manuscript. The article presents a detailed description of the manuscript; it follows the path of the many places the codex passed through from the days of its creation until the present time; it offers a thorough line of argument that proves on one hand that the manuscript from New Haven is in fact identical to the one that disappeared from Gotha, and that verifies on the other hand an assumption by the renowned researcher Hans-Peter Hils that it is identical to yet another believed-to-be-lost manuscript that was sold by auction in Heidelberg in the 1950s and 1960s as single leaves; and finally it makes an attempt to reconstruct the original structure of the manuscript after it had been pulled apart.